Wage dispersion: Empirical developments, explanations, and reform options - Hansjörg Herr; Bea Ruoff (International Labour Organization (ILO), 2014)
Market driven wage dispersion is a critical feature of income inequality. In this paper especially the Keynesian perspective on how to explain the global trends of rising wage dispersion is elaborated. Special attention is given to the policy implications derived from the analysis. Keynesian theory suggests that wage dispersion is a result of weaker trade union power, a lack of wage bargaining coordination and an erosion of labour market institutions after the begin of the market radical globalisation project in the 1970s/1980s. These developments are interrelated with the deregulation of financial markets, shareholder value corporate governance systems, extensive outsourcing and permanent deep economic shocks which are directly connected with the type of globalisation that developed during the last decades. Institutional changes to reduce wage dispersion and at the same time active demand management to guarantee high employment are recommended.
Keywords: 330; wage rate; wage determination; trade union attitude; employment; economic theory; trend